Simvastatin regulates the proliferation, apoptosis, migration and invasion of human acute myeloid leukemia cells via miR-19a-3p/HIF-1α axis. Issue 2 (20th December 2021) - Tian, Hua; Qiang, Tiao; Wang, Jinbo; Ji, Li; Li, Bo
ABSTRACT: Statins are mainly used to lower plasma cholesterol level. In addition, the anti-leukemia effect of statins has been reported, but the mechanism remains unclear. This study aimed to explore the bioregulation of simvastatin and its mechanism in acute leukemia cell lines. Cell viability was detected by CCK-8 analysis. Apoptosis was detected through flow cytometry. Cell invasion and migration both were observed by transwell and wound healing separately. RT-qPCR and Western blot were used for determination of genes and proteins. We found that that simvastatin could regulate the biological functions of acute myeloid leukemia (AML) cells, including its proliferation, migration, invasion and apoptosis, which may be carried out by down-regulating miR-19a-3p. Overexpression of miR-19a-3p had the opposite effect in AML cells, suggesting simvastatin-inhibited AML by reducing miR-19a-3p expression. Following researches showed that HIF-1α was directly regulated by the target of miR-19a-3p. Simvastatin could reverse the adverse effects caused by miR-19a-3p mimics. Conversely, the increased expression of Mcl-1, the inhibition of caspase-3 could promote the growth of AML cells. In conclusion, simvastatin could inhibit the proliferation, migration, invasion and promote apoptosis in AML cells through miR-19a-3p/HIF-1α axis.